Development of Hot Trub and Coffee Silverskin Phytoextracts for Sustainable Aerosol Disinfectant Application - James Ziemah; Matthias S. Ullrich; Nikolai Kuhnert (Foods)
Chemical products, including cleaning agents, disinfectants, stain removers, and cosmetics, release harmful chemicals that pose a risk to human health and the environment, necessitating alternative sources. The objective of this research was to identify the most effective phytoextract from food production waste for use in sustainable aerosol hygiene technology as an electrostatic bio-disinfectant. The investigation was performed through wipe tests and airborne microbial collection techniques. The upgraded coffee silverskin phytoextract demonstrated superior disinfection potential for various surfaces and airborne microbes compared to the hot trub phytoextract, with an industrial disinfectant serving as the control. Log reduction analyses revealed a more significant killing efficacy (p ≤ 0.05, using the ANOVA test) against Gram-positive organisms (Bacillus subtilis and Listeria monocytogenes) than against Gram-negative organisms (Escherichia coli and Vibrio parahaemolyticus), with the log reductions ranging from 3.08 to 5.56 and 3.72 to 5.81, respectively. Chemical characterization by LC-ESI-QTOF-MS, 1H NMR, and FTIR showed that CGAs and chalcones are the most bioactive compounds in CSS and HT, respectively. The innovation in this work involves an integrated approach that combines waste-derived phytoextracts, advanced chemical profiling, and scalable aerosol disinfection. Furthermore, this research offers a greener, cost-effective, and industrially relevant alternative to synthetic chemical disinfectants. The interdisciplinary approach contributes to the development of bio-based disinfectants for use in the food industry, hospitals, and public health settings. This investigation supports a paradigm shift toward sustainable disinfection practices, thereby improving food and environmental safety.